Chiral Oligothiophenes with Remarkable Circularly Polarized Luminescence and Electroluminescence in Thin Films. Issue 70 (12th November 2020) - Albano, Gianluigi; Aronica, Laura Antonella; Minotto, Alessandro; Cacialli, Franco; Di Bari, Lorenzo
Abstract: This work reports the first observation of circularly polarized electroluminescence (CPEL) in thin films of self‐organized oligothiophenes. Four new 1, 4‐phenylene and 9 H ‐carbazole‐based oligothiophenes were ad hoc designed to ensure efficient spontaneous formation of chiral supramolecular order. They were easily synthesized and their chiroptical properties in thin films were measured. Circularly polarized luminescence (CPL) spectra revealed glum in the order of 10 −2 on a wide wavelengths range, originating from their self‐organized chiral supramolecular organization. These molecules have reasonable properties as organic semiconductors and for this reason they can constitute the active layer of circularly‐polarized organic light‐emitting diodes (CP‐OLEDs). Thus, we could investigate directly their electroluminescence (EL) and CPEL, without resorting to blends, but rather in a simple multilayer device with basic architecture. This is the first example of a CP‐OLED with active layer made only of a small organic compound. Abstract : Chiroptical properties in thin films of four new chiral oligothiophenes ad hoc designed and synthesized were investigated. Remarkable circularly polarized luminescence (CPL) and electroluminescence (CPEL) were observed on a wide wavelength range, originating from their chiral supramolecular organization. This is the first observation of CPEL in thin films of chiral oligothiophenes.